PENGARUH HARGA DAN KUALITAS JASA TERHADAP LOYALITAS PELANGGAN HOTEL EMERSIA DI BANDAR LAMPUNG - Winata, Andri; Fiqri, Isnawan Ahlul (Jurnal Manajemen Magister Darmajaya, 2017)
Emersia Hotel is a four-star hotel located in the center of the town of Bandar Lampung on Jl. Robert Wolter Mongonsidi 70 Bandar Lampung. The problem in this research was the price at Emersia was lower but the number of customers decreased in each month and there were still customers who complained about the quality of service provided by Emersia Hotel. The aim of this research was to know the effect of price and service quality on customer loyalty of Emersia Hotel in Bandar Lampung, The data used were primary and secondary data. The population in this study was the customers in 2015 amounting to 242 customers atÂ  Emersia Hotel Bandar Lampung. With the sample of 71 respondents. This research was a quantitative research and sampling used purposive sampling method. The results of data analysis and hypothesis testing obtained determinant coefficient value R Squares amounted to 0,425 (42.5%) of consumer loyalty influenced by price (X1) and quality of service (X2), and the remaining 57.5% was influenced by factors or other variables. meanawhile the relationship of price and quality of services along with customer loyalty was equal to 0.652 (65.2%). Based on the result of data analysis, it is found that the price (X1) influence on customer loyalty (Y) of the Emersia Hotel in Bandar Lampung, service quality (X2) influence to customer loyalty (Y) of the Emersia Hotel in Bandar Lampung, price (X1) and services (X2) simultaneously influenced to the customer loyalty (Y) of the Emersia Hotel in Bandar Lampung.Keywords: Price, Quality of Service and Customer Loyalty